2018
DOI: 10.1371/journal.pone.0202109
|View full text |Cite
|
Sign up to set email alerts
|

HCV elimination among people who inject drugs. Modelling pre- and post–WHO elimination era

Abstract: BackgroundElimination of hepatitis C virus (HCV) among people who inject drugs (PWID) is a costly investment, so strategies should not only focus on eliminating the disease, but also on preventing disease resurgence. The aims of this study are to compute the minimum necessary antiviral therapies to achieve elimination with and without the additional expansion of harm reduction (HR) programs and to examine the sustainability of HCV elimination after 2030 if treatment is discontinued.MethodWe considered two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
3
24
0
5
Order By: Relevance
“…Based on our systematic review, we also suggest that certain factors may influence the measured reinfection rates seen among PWID in upper and lower middle-income countries. Past epidemiological studies have shown that higher background HCV prevalence is associated with a higher risk of reinfection rates among people actively engaged in high-risk injection behavior (e.g., sharing needles or equipment) [ 28 ]. Modeling studies have applied this understanding and generally agree that “treat all” mandates are highly cost-effective if the background HCV prevalence in the source population is below 50% [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our systematic review, we also suggest that certain factors may influence the measured reinfection rates seen among PWID in upper and lower middle-income countries. Past epidemiological studies have shown that higher background HCV prevalence is associated with a higher risk of reinfection rates among people actively engaged in high-risk injection behavior (e.g., sharing needles or equipment) [ 28 ]. Modeling studies have applied this understanding and generally agree that “treat all” mandates are highly cost-effective if the background HCV prevalence in the source population is below 50% [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past epidemiological studies have shown that higher background HCV prevalence is associated with a higher risk of reinfection rates among people actively engaged in high-risk injection behavior (e.g., sharing needles or equipment) [ 28 ]. Modeling studies have applied this understanding and generally agree that “treat all” mandates are highly cost-effective if the background HCV prevalence in the source population is below 50% [ 28 , 29 ]. Among studies in our review, however, background prevalence did not appear to have a significant impact on reinfection rates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous discrete‐time, stochastic, individual‐based model of HCV transmission among PWID was used . In short, the model follows transitions concerning HCV infection between three mutually exclusive compartments of PWID: (a) susceptible people including those who either have never been HCV‐infected, have cleared infection or have had successful treatment; and (b) HCV‐infected.…”
Section: Methodsmentioning
confidence: 99%
“…After infection, PWID have a probability of clearing the disease spontaneously and are then at risk of re‐infection; to be conservative, we assumed that the risk of re‐infection was equal to the initial infection rate; those who do not clear the infection progress to the chronically infected stage. Further details about the description of the model are available in the appendix or elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Recent data from the DAA era suggest that less than 20% of HCV‐infected PWID in different global settings have ever received HCV treatment 17‐19 . To achieve HCV elimination goals, HCV treatment uptake among PWID must increase 20 . Patient, provider and system level barriers have been extensively detailed in previous research and have been linked to low treatment uptake among PWID 21‐25 …”
Section: Introductionmentioning
confidence: 99%